STRATEGI KEPALA SEKOLAH DALAM MENINGKATKAN BUDAYA MUTU DAN DAYA SAING SEKOLAH DI SMA BRAWIJAYA SMART SCHOOL MALANG - Amiga Putri Minanda (Program Studi Manajemen Pendidikan Islam Fakultas Ilmu Tarbiyah dan Keguruan UIN Maulana Malik Ibrahim Malang, 2023)
Strategy is the art of using the existing skills and resources of an organization to achieve its goals through effective relationships with the environment in the most favorable conditions. In building a culture of quality and competitiveness, the principal is a leader who has an important role. Principals must have a serious attitude and a high work ethic so that they can produce mature strategies. The strategy aims to make change truly materialized by the birth of new innovations that have an impact on improving the quality and competitiveness of education in schools.The focus of this research is 1) how is the principal's strategic planning in improving the quality culture and school competitiveness at SMA Brawijaya Smart School Malang? 2) how is the implementation of the principal's strategy in improving the quality culture and school competitiveness in SMA Brawijaya Smart School Malang? 3) how are the results of the principal's strategy in improving the quality culture and school competitiveness at SMA Brawijaya Smart School Malang?The research method used is a qualitative research method with a case study approach. Qualitative research is a form of research in which data is collected and analyzed in the field to draw conclusions. The case study approach is intended to describe an in-depth study of how the principal's strategy in improving the quality culture and school competitiveness at SMA Brawijaya Smart School Malang.This study shows the results that: 1) Principal's Strategic Planning in Improving Quality Culture and School Competitiveness at SMA Brawijaya Smart School Malang, namely: a) The principal's plan or strategy is realized in the form of self-planning and strategic plan in accordance with the vision, mission, and school goals. b) Decisions on the strategic plan are taken through a meeting together with the deputy head which is held once a week, the principal holds a meeting with the vice principal and together with the teacher through an official meeting which is held once a month. b) Planning in quality culture applied in SMA Brawijaya Smart School Malang is SMART quality culture. c) Plan for school competitiveness by providing excellent service, improving teacher and employee performance, and implementing superior programs. 2) Implementation of the Principal's Strategy in Improving the Quality Culture and School Competitiveness, namely: a) The principal tries to facilitate the talents and interests of students through the procurement of superior programs and provides 16 kinds of extracurricular activities. b) Improving superior programs that are always improved, providing quality teachers, providing optimal educational support facilities, very strategic school locations, and making schools that are directly proportional to price and service. c) Teachers and education staff provide a lot of information and are open to parents and the community. 3) The results of the principal's strategy in improving the quality culture and school competitiveness are that: a) there are several obstacles in the leadership of the principal but the principal tries to evaluate it through meetings with the vice principal as well as teachers and staff. b) Successfully won various competitions, ranging from academic to non-academic. c) Ranked 13th based on LTMPT with the highest average UTBK score that competes with other public/private SMA/MA in Malang city, thus making SMA Brawijaya Smart School Malang as one of the favorite private schools in Malang City.